Investigation over/under-voltage protection of passive islanding detection method of distributed generations in electrical distribution systems - Yingram, Manop; Premrudeepreechacharn, S. (2012 International Conference on Renewable Energy Research and Applications, 2012)
The objective of this paper is to investigate over/under-voltage protection (OVP/UVP) of passive islanding detection method of distributed generations in electrical distribution systems. The IEEE 14-bus system is simulated with Powerworld simulator. The studies show relationship between load and NDZ with DG in power system. The simulation results have showed that the change of load will affect the rate of transfer of ΔP uneven. If OVP/UVP of passive islanding detection method used algorithm with ΔP/P equation for decision, it may not be able to detect islanding condition In addition, if the multiple DGs in electrical distribution systems can replace active power of utility system, the OVP/UVP of passive islanding detection method cannot detected the state of islanding.